Narratives of Dependency: Textual Representations of Slavery, Captivity, and Other Forms of Strong Asymmetrical Dependencies - Brüggen, Elke; Gymnich, Marion (Dependency and Slavery Studies, 2024)
The 15 articles in this interdisciplinary volume examine facets of the history of asymmetrical dependencies via representations of dependency in a wide range of (factual and fictional) text types, including inscriptions from Egyptian tombs, biblical narratives, novels from antiquity, the Middle High German Rolandslied, Ottoman court records, travelogues, the American gift book The Liberty Bell, and oral narratives by Caribbean Hindu women.